Separating Convective from Diffusive Mass Transport Mechanisms in Ionic Liquids by Redox Pro-fluorescence Microscopy - Belotti, Mattia; El-Tahawy, M.M.T.; Garavelli, M.; Coote, M.L.; Iyer, K.S.; Ciampi, Simone (2023)
The study of electrochemical reactivity requires analytical techniques capable of probing the diffusion of reactants and products to and from electrified interfaces. Information on diffusion coefficients is often obtained indirectly by modeling current transients and cyclic voltammetry data, but such measurements lack spatial resolution and are accurate only if mass transport by convection is negligible. Detecting and accounting for adventitious convection in viscous and wet solvents, such as ionic liquids, is technically challenging. We have developed a direct, spatiotemporally resolved optical tracking of diffusion fronts which can detect and resolve convective disturbances to linear diffusion. By tracking the movement of an electrode-generated fluorophore, we demonstrate that parasitic gas evolving reactions lead to 10-fold overestimates of macroscopic diffusion coefficients. A hypothesis is put forward linking large barriers to inner-sphere redox reactions, such as hydrogen gas evolution, to the formation of cation-rich overscreening and crowding double layer structures in imidazolium-based ionic liquids.